Encyclopedia of southern literature - Snodgrass, Mary Ellen (Santa Barbara, Calif. : ABC-CLIO, 1997)
Alphabetically arranged survey of southern literature, containing biographical and literary history, bibliographical citations, critical commentary, and cross-references.
Includes bibliographical references (p. 485-527) and index.
Book Report.
Choice.
Wilson's Senior High School.
Adult
Keywords: American literature -- Southern States -- Encyclopedias; American literature -- Southern States -- Encyclopedias; Southern States -- In literature -- Encyclopedias; Southern States -- Intellectual life -- Encyclopedias; Southern States in literature -- Encyclopedias; Southern States -- Intellectual life -- Encyclopedias